Russian public sector employees' reasoning of ethical behavior: an empirical study - Ermasova, Natalia et al (2018)
The purpose of this study is to examine the ethical reasoning of Russian public sector employees based on age, gender, management experience, specialization by the area of activity, and tenure with the current employer. Using t-test and one-way ANOVA statistical analyses, this study analyzed the ethical reasoning of 199 Russian public sector employees. Significant differences in ethical reasoning were observed among public sector employees based on age and specialization by the area of activity, but no significant differences in ethical reasoning were found among respondents based on gender, management experience and tenure with current employer. - Reproduced.
Keywords: Ethics - Russia; Government enterprise - Personnel - Russia; Public sector - Russia